SISTEM INFORMASI MANAJEMEN PHOTOGRAPHY PADA DOMINO PRODUCTION BERBASIS WEB: Information System, Management, Photography, Promotion, Website - Pariyadi; Ramadani, Muhammad (JURNAL AKADEMIKA, 2023)
Domino Production currently in terms of public communication and promotion still uses brochures, word of mouth and viewing Instagram. This is already good, but it can be improved and reach more people who know Domino Production with a website. The ordering process that is done manually still uses a simple method, namely ordering just like that without any reports, so it is necessary to build an application that aims to facilitate ordering and reports. In the process of making and designing a photography management information system at Domino Production using the PHP programming language and using the MySql database. The research method used by researchers in preparing this practical work is to use the Waterfall method. Researchers carry out system development with design analysis, system design and Data Flow Diagrams (DFD). The system created will produce output that can display ordering data on a product ordered through a customer. With the existence of a Photography Management Information System on Web-Based Domino Production, it is hoped that it will make it easier to carry out promotions and can increase the number of orders for Photography services.